2021
DOI: 10.18421/tem103-31
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Students’ Cyber Ethics Awareness in a Gender-Segregated Environment Under the Impact of COVID-19 Pandemic

Abstract: Cyber ethics are essential components of information technology. The COVID-19 situation has brought unprecedented challenges to traditional higher education institutions, especially for students using their electronic devices in all their learning activities. This study focused on cyber ethics perceptions among university undergraduates’ students during COVID-19 conditions. It aims to analyze the extent to which distinct attributes, such as gender, education level, grades, or Cumulative Grade Point Average (CG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Moreover, the percentage of those who found computer ethics valuable and interesting increased to a substantial 85%. These results underscore the transformative power of education and awareness campaigns, especially when combined with information fusion technologies [26,44]. This finding aligns with the principles of community building in cyberspace, promoting common development and progress, and underscores the importance of open, equal, collaborative, and shared platforms for enhancing cyberculture [34].…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Moreover, the percentage of those who found computer ethics valuable and interesting increased to a substantial 85%. These results underscore the transformative power of education and awareness campaigns, especially when combined with information fusion technologies [26,44]. This finding aligns with the principles of community building in cyberspace, promoting common development and progress, and underscores the importance of open, equal, collaborative, and shared platforms for enhancing cyberculture [34].…”
Section: Discussionsupporting
confidence: 61%
“…Comparing these results with Guo et al [15] and Nagahawatta and Warren [27], it can be observed a significant shift in the way computer ethics are perceived and practiced. Traditional computer ethics primarily focused on the ethical aspects of computer activities among individuals [26]. However, the findings indicate a transition from individual‐centric computer ethics to the broader concept of network ethics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation